Peningkatan Aktivitas Belajar Dan Hasil Belajar Siswa Pada Materi Hak Asasi Manusia Dalam Terang Kitab Suci Dan Ajaran Gereja Dengan Model Problem Based Learning (PBL) Pada Siswa Kelas XI Saint John Catholic School - Hermanus Agun (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Good education is the main foundation for the progress of a nation. In the era of globalization and intensified competition, the good education is the key to prepare the young generation to face the challenges of the future. Through the good education, young people are given the opportunity to develop their creative thinking, problem-solving and technological skills needed in the face of a rapidly changing world. Furthermore, good education is also an important pillar in a democratic system. Young people who receive a good education tend to have the ability to think critically, analyzing information, and participate actively in the political process. Recognising the importance of education, the Indonesian nation pays much more attention to the issue of education, even the objectives are increasingly refined. This is in accordance with the provisions contained in the preamble of the 1945 Constitution. Broadly speaking, education is an effort to educate the nation's life in order to become a whole human being with the spirit of Pancasila. The Law of the Republic of Indonesia No. 20 of 2003 on the National Education System also states as follows: